Analisis Pengendalian Intern Penerimaan dan Pengeluaran Kas dalam Meningkatkan Kualitas Cash Flows (Studi Kasus pada PT Smart Living) - Rochmah, Shofiatur; Kustiningsih, Nanik (JURNAL AKUNTANSI DAN MANAJEMEN, 2021)
Internal control on cash receipts and disbuements in the company is vey important because cash is one of the assets that has an important role in the development of the company, where cash is the most liquid asset. This study aims to analyze the internal control of cash receips and disbursements in improving the quality of cash flows carried out at PT. Smart Living which is engaged in GPS installation services. In this study, the method used by the autho in analyzing the data is a qualitative method using inteview, observation, and documentation. The results of this study indicate that the internal control system for cash receipts has been unning effectively, wich has not been running effectively, because there are still dual function between recipients, depositors and cash registers.